If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 7 = -2x + 7 Reorder the terms: 7 + 2x = -2x + 7 Reorder the terms: 7 + 2x = 7 + -2x Add '-7' to each side of the equation. 7 + -7 + 2x = 7 + -7 + -2x Combine like terms: 7 + -7 = 0 0 + 2x = 7 + -7 + -2x 2x = 7 + -7 + -2x Combine like terms: 7 + -7 = 0 2x = 0 + -2x 2x = -2x Solving 2x = -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 2x + 2x = -2x + 2x Combine like terms: 2x + 2x = 4x 4x = -2x + 2x Combine like terms: -2x + 2x = 0 4x = 0 Divide each side by '4'. x = 0 Simplifying x = 0
| 9(b-4)-7b=5(3b-10) | | 1/12y=15 | | 8+4b=18 | | 3/7=-4/x+5 | | (-5/c)=(1/3) | | 1/4(20-4x)=6-x | | 12-q=8 | | x+7/3=7 | | (2/7)=(x/-42) | | -4-x=6x-4 | | y-8+6y=-9+5y+1 | | 12=e/12 | | 7x+8=8+6x | | 4x+11=5x+4 | | x+1.35=2 | | -4/7-1/2v=-2/3 | | 3w=4w+-10 | | (7/10)*(4/5) | | 3-4x=2x+21 | | (x/4)=(3/2) | | 44=28-4(x-2) | | 5/14=p/49 | | 5x+10=-100 | | -4x+7=-6x+17 | | E/12=13 | | 20-d=13 | | 15-3y+2=5 | | 4((x^2)-6x+9)=192 | | 8.5-32=-82 | | 1/4(x-4)=-4 | | 32x^2+56x+12= | | -6x-6=6x+126 |